Australian University Teaching Criteria and Standards Project : Final Report. - Chalmers, Denise; Cummings, Rick; Elliott, Sofia; Stoney, Sue; Tucker, Beatrice; Wicking, Rachel; Jorre de St Jorre, Trina (Office for Learning and Teaching, 2014)
A considerable amount of research has been undertaken and published recently on what constitutes excellent teaching in higher education. However, this has not been synthesised or developed into a coherent framework. This report documents the outcomes of the 'Australian University Teaching Criteria and Standards' project which was commissioned by the Office of Learning and Teaching (OLT) as part of their strategic priority 'Professionalisation of the Academic Workforce' project. The project was conducted over an 18 month period commencing in September 2012 through to February 2014.